2016
DOI: 10.1016/j.jmbbm.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Mini-interfacial fracture toughness as a new validated enamel-bonding effectiveness test

Abstract: mini-iFT appeared a valid alternative method to assess the mechanical properties of adhesive-enamel interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…While a reliable bonding to enamel has been established decades ago, the current results demonstrate that the enamel marginal seal is still at risk. Enamel gaps were more extensive in the 1-SEAs than in 2-SEAs, which is in line with previous reports on lower enamel bond strength (Pongprueksa et al 2016) and higher microleakage of the former (Schwendicke et al 2015). Another important finding was the development of postcuring enamel cracks along the enamel walls of some specimens (Appendix Fig.…”
Section: Discussionsupporting
confidence: 90%
“…While a reliable bonding to enamel has been established decades ago, the current results demonstrate that the enamel marginal seal is still at risk. Enamel gaps were more extensive in the 1-SEAs than in 2-SEAs, which is in line with previous reports on lower enamel bond strength (Pongprueksa et al 2016) and higher microleakage of the former (Schwendicke et al 2015). Another important finding was the development of postcuring enamel cracks along the enamel walls of some specimens (Appendix Fig.…”
Section: Discussionsupporting
confidence: 90%
“…(1) Ideally, bonding effectiveness should be measured by determining the strength of the adhesive interface solely, which can be achieved best using a fracture toughness approach. (16) In this study fracture toughness test was used as its values are not test-dependent and also less affected by random flaws in the test specimens so, better comparable, and less variable and more universal values.…”
Section: Discussionmentioning
confidence: 99%
“…3 ), may suffer from smear-layer interference and thus explain the lower fracture toughness. In another study, the lowest interfacial fracture toughness onto enamel was found for the adhesives applied following a one-step self-etch approach ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fracture toughness test is considered a more valid method to assess bonding effectiveness compared with conventional bond strength testing ( 13 ). However, to date, only few studies have measured fracture toughness using various methodologies ( 12 - 15 ).…”
Section: Introductionmentioning
confidence: 99%